Analisis pengaruh inflasi, pertumbuhan ekonomi, Harga emas, kurs dollar dan SBI terhadap IHSG - WS, Paidi; Sasono, Heri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to analyze the effect of Macro Variables on the Composite Stock Price Index (JCI) for the period 2010 to 2021. The macro variables used in this study were Inflation, Economic Growth, Gold Price, Dollar Exchange Rate and SBI (7-Day Reverse Repo Rate). The research sample year are 12 years, starting from 2010 to 2021. Research analysis using multiple linear regression analysis, t test, F test, coefficient of determination test using SPSS Version 26 software. The conclusion of the study are that Economic Growth, Gold Price, Dollar Exchange Rate has a significant effect on the JCI, while the Inflation and SBI (7-Day Reverse Repo Rate) has not significant effect on the JCI.